KAJIAN TERHADAP FAKTORYANG MEMPENGARUHI IMPULSE BUYINGDALAM ONLINE SHOPPING - Yosy Cynthia Miranda (Kompetensi (Competence : Journal of Management Studies), 2016)
Purchase impulsively already become a lifestyle nowadays. Supported by increasing advanced in information technology, make impulse buying not only happen at retail stores, but also on online shopping. Now, online shopping has become a part of public life. Consumers can get many benefits if they make a purchase via online. a lot of convenience and promotion they could find if they shop via online that they would not find if they shop directly in retail stores. That is what causes counsumers start to move for shop via online. Therefore,, marketers,  start to applying strategies for increasing sales in online shopping by using impulsive consumers character. For that, marketers should be knowing what factors are effective can increase consumers buying interest impulsively in the sales online. In previous researches, known fact that external factor have a dominant influence for increasing consumers buying interest impulsively than internal factors. External factors which influence impulse buying on online shopping consists of service quality and promotion. While internal factors which influence impulse buying on online shopping consists of positively emotional and gender.positively emotional factor and gender factor are based on consumer self so, online seller can not  directly influence consumers buying interest because consumers may not be interacted directly with virtual shop attribute.